THE INFLUENCE OF LEARNING CLIMATE AND LEARNING STYLES ON CREATIVITY IN PRIMARY ISLAMIC EDUCATION - Mustofa Tohari; Syaiful, Syaiful; Mukminin, Moh. Amiril; Dauda, Rafat B (Al-Mudarris: Journal Of Education, 2025)
This study aims to analyze the influence of learning climate and learning styles on students' creativity in Islamic Education. Employing a quantitative approach with a correlational design, the research involved 42 respondents selected through purposive sampling. Data were collected using questionnaires to measure learning climate, learning styles, and student creativity, and subsequently analyzed using multiple linear regression. The findings indicate a significant positive influence of both learning climate and learning styles on students' creativity. Specifically, the regression analysis yielded coefficients of 0.240 for learning climate and 0.269 for learning styles, confirming that both variables contribute significantly to the outcome. The Adjusted R Square value of 0.148 reveals that learning climate and learning styles explain 14.8% of the variance in student creativity, while the remaining 85.2% is attributed to other factors outside the scope of this study. These results suggest that optimizing the classroom environment and accommodating diverse learning preferences are essential, though not exclusive, strategies for fostering creativity.